A new catalyst based on disposed red mud for the efficient electrochemical reduction of nitrate-to-ammonia. Issue 2 (21st October 2022) - Xu, Yan-Tong; Ren, Ke-Cheng; Tao, Zui-Miao; Sam, Daniel Kobina; Feng, Enlang; Wang, Xiang; Zhang, Gengming; Wu, Junchi; Cao, Yan
Abstract : A sustainable red mud disposal solution is proposed based on the emerging electrocatalytic nitrate-to-ammonia reduction reaction, exhibiting outstanding performance and efficient energy conversion compared to many other synthetic catalysts. Abstract : Many concerns have been raised about ecological and environmental risks from the disposal of red mud (RM) in the aluminium industry. For a long time a suitable use for RM, due to the huge amount produced, has been needed. This study, for the first time, applies RM as an efficient electrochemical catalyst in the emerging nitrate-to-ammonia reduction reaction (NARR) based on renewable energy, in which the produced green ammonia can supply energy for rechargeable ammonia energy storage (RAES). The performance of RM stands out among many other synthetic catalysts in the NARR as well as further combination with photovoltaic technology. Specifically, it exhibits a superior faradaic efficiency toward NH3 of 92.8% and an NH3 formation rate of 0.16 mmol cm −2 h −1 under −0.73 V ( vs . reversible hydrogen electrode) in a neutral phosphate buffer solution with 1.0 M NO3 − . The energy efficiency toward NH3 is over 30% in a two-electrode system, and that of the solar-to-NH3 conversion is 2.09% at a light intensity of 0.06 W cm −2 based on a commercial poly-Si photovoltaic cell. The results promise a low-cost RM catalyst for the NARR sustainable route, realizing RM recycling and zero-carbon ammonia-energy production.